Analisis Strategi Pemasaran Dalam Perspektif Manajemen pada Koperasi Desa Merah Putih - Nashihuddin Sahil Alfikri; Hendra Riofita (MANAJEMEN, 2026)
The development of digital technology has significantly transformed marketing practices across various organizations, including community-based economic institutions such as cooperatives. Village-level cooperatives still face several limitations in developing adaptive marketing strategies to respond to the increasingly competitive business environment. This study aims to analyze marketing strategies from a management perspective in the Merah Putih Village Cooperative, particularly in relation to digital marketing development, changes in consumer behavior, and the utilization of digital payment systems. This research employs a qualitative approach using a literature review method based on various scientific journals and relevant academic references. The data analysis technique uses descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The results show that cooperative marketing strategies are still largely dominated by conventional approaches that rely on direct interaction and community social networks. However, the utilization of digital marketing through social media and digital platforms has significant potential to expand market reach and improve marketing communication effectiveness. In addition, perceived value and the convenience of transactions through digital payment systems also influence consumer purchasing decisions. From a management perspective, the success of cooperative marketing strategies is strongly influenced by managerial capabilities in planning, organizing, implementing, and evaluating marketing strategies in an integrated manner. Therefore, cooperatives need to optimize the use of digital technology and improve human resource competencies in order to enhance competitiveness in the era of digital transformation.